Polymorphic microsatellite loci for Haumania danckelmaniana and transferability to H. liebrechtsiana (Marantaceae)(1) - Ley, Alexandra C. (Appl Plant Sci, 2016)
PREMISE OF THE STUDY: Microsatellite markers were developed for the species Haumania danckelmaniana (Marantaceae) from central tropical Africa. METHODS AND RESULTS: Microsatellite isolation was performed simultaneously on three different species of Marantaceae through a procedure that combines multiplex microsatellite enrichment and next-generation sequencing. From 80 primers selected for initial screening, 20 markers positively amplified in H. danckelmaniana, of which 10 presented unambiguous amplification products within the expected size range and eight were polymorphic with four to nine alleles per locus. Positive transferability with the related species H. liebrechtsiana was observed for the same 10 markers. CONCLUSIONS: The polymorphic microsatellite markers are suitable for studies in genetic diversity and structure, mating system, and gene flow in H. danckelmaniana and the closely related species H. liebrechtsiana.